Full Learning: Bibliometric Insights into Deep Learning Pedagogies Approach Integration in Physics Education - Yuslikha Al Mudhotin; Nabila Nur Almaida Nasution; Amelia Putri Ristyawardani; Nadi Suprapto (Jurnal Pendidikan Sains Indonesia, 2026)
Physics education in some schools still uses conventional methods, which focus on memorizing physics concepts without involving other aspects. Such methods lead students to view physics as uninteresting, difficult, and abstract. Therefore, in order for students to understand better and be more enthusiastic about each physics lesson, there is a need for innovative teaching. One way is to integrate a deep learning pedagogy approach into the curriculum. This approach has three main elements: meaningful, mindful, and joyful learning, often referred to as full learning (FL3). This new approach aims to encourage students to have a more in-depth learning experience. However, this approach is still rarely studied in depth for physics learning. Therefore, this study was conducted with the aim of clearly visualizing the principles of FL3 in the field of education. Researchers used bibliometric analysis methods to visualize the data with VOSviewer and RStudio to identify co-occurrences, and MS Excel for descriptive statistical analysis. After collecting data from scopus, the results showed a significant increase in publications over the last ten years, particularly in 2019, when the initial research topic focused on educational technology but shifted over time towards contextual learning. From the three main dimensions of FL3, meaningful learning can be developed and applied through experiments and ethnoscience, mindful learning through reflective assessment, and joyful learning through gamification and experience-based activities. These findings confirm that FL3 has great potential to shape a physics learning model oriented towards deep understanding, reflective awareness, and continuous learning motivation in 21st-century education